Geological record of meltwater events at Qinghai Lake, China from the past 40 ka. (1st October 2016) - Zhou, Weijian; Liu, Taibei; Wang, Hao; An, Zhisheng; Cheng, Peng; Zhu, Yizhi; Burr, G.S.
Abstract: We report here on a previously unpublished sediment core from Qinghai Lake, China, that preserves a continuous record of sedimentation for the past 40 ka. A striking feature of the record is a set of distinct meltwater events recorded at 35, 19 and 14 ka respectively. These events are manifest as distinct pulses of relatively old organic radiocarbon in the sediments. We interpret these as a signal of glacial melting in the Qinghai Lake watershed. The meltwater signals are closely correlated to temperature and precipitation records associated with deglaciation. The events at 19 ka and 14 ka correspond to well-established high latitude Melt Water Pulse (MWP) events during Marine Isotope Stage (MIS) 2, and the 35 ka event corresponds to a period of pervasive high lake levels in western China during late MIS 3. We interpret these anomalous dates as the result of relatively old carbon that was destabilized by the glaciers, and released into the lake as the glaciers melted. The data indicate that this process takes thousands of years. We expect that the approach employed here to identify these events is generally applicable to any lake system with a significant glacial meltwater component. Highlights: We present a record of sedimentation at Qinghai Lake that provides a continuous coverage for the past 43 ka. We use radiocarbon data to detect three deglaciation events, which has potential value for glacial meltwater input. We combine lake studies with studies on land, both records show evidence for warming at about 35 ka.